Role Of Cooperative Units Of Sungai Source Of Sustenance Village In Helping The Economy Of Oil Palm Farmers In Sungai Putih Village In 2022 (Case Study Of Sungai Putih Village Community) - Ade Taufan; Ira Susanti (Institute of Computer Science (IOCS), 2022)
Cooperatives are an appropriate forum to fight for the interests of members from both the legal and government aspects. Through these efforts, the members of the cooperative live in peace and use the functions of the Village Unit cooperative as a whole. With the success of the KUD in facilitating farmers in providing what they need and the farmers being successful in their business, the farmers will invest their funds to create new gardens, which will automatically require new workers in addition to the existing workforce to maintain existing gardens in the business field. This study aims to determine the role of the Sumber Sustenance Village Unit Cooperative in improving the economic standard of living of the community. This study uses data collection techniques with interviews and documentation. Based on the results of the study, that the role of the Sumber Rezeki Village Unit (KUD) cooperative can implement its cooperative role. With the existence of the Sungai Putih Village farmer's economic cooperative, it can realize income, equitable prosperity and improve the member's economy and meet secondary needs.